INNOVATIONS IN EDUCATION DRIVEN BY ARTIFICIAL LEARNING TECHNOLOGIES ARE TRANSFORMING TRADITIONAL TEACHING METHODS AND ENHANCING PERSONALIZED LEARNING EXPERIENCES - Dinara Xoshimova; Nafisa Ahmadjonova (“SUN’IY INTELLEKTNING TIL O‘RGANISHDAGI O‘RNI” MAVZUSIDA TALABALAR ILMIY-AMALIY KONFERENSIYASI, 2025)
This article explores innovations in education, including technological advancements, personalized learning, e-learning, virtual and augmented reality applications, and their impact on modern educational environments. It highlights benefits, challenges, and future trends in education.